Study on Mechanical Properties of Epoxy Composite with Natural Reinforcement - Coir Fiber and Dates - Anbusezhian, S; Miji, Milun Tom; MC, Vishnu Vijayan (Journal of Advanced Research in Mechanical Engineering and Technology, 2023)
The mechanical way of behaving of coir-built up Epoxy Sap Composite is to be explored. Normally happening coir fiber are utilized as support while thermosetting polymer pitch epoxy is utilized as network material. The normal fiber enjoys an upper hand over inexhaustible assets and has high promoting claim. To diminish the dampness ingestion conduct of coir fiber, it is synthetically treated with 5% Sodium Hydroxide (NaOH). This substance treatment diminishes the liking of fiber towards material and increments surface harshness subsequently bringing about better framework support interface holding. Both crude and treated coir tests were used for the creation. Coir fiber built up Epoxy tar bio composite were fabricated utilizing pressure shaping. Regular fiber supported polymer composite act as a significant choice to man-made fiber built up polymer composite since they are richly accessible, practical, recyclable and biodegradable having a high mechanical strength and are rapidly jumping up concerning research and modern applications. The fundamental goal is to evaluate the mechanical properties of coir fiber with epoxy polymer along with date seed powder utilized as filler material. The example was manufactured with coir at different elements of coir like distance across, length and content along with date seed powder. Pliable, flexural and influence were led in the pre-arranged composite materials according to the method of ASTM standard. From the outcome we observed that the effect strength is more when dates seed powder is utilized as filler material with coir fiber and epoxy sap. How to cite this article: Anbusezhian S. Study on Mechanical Properties of Epoxy Composite with Natural Reinforcement - Coir Fiber and Dates. J Adv Res Mech Engi Tech 2023; 10(1): 1-5. DOI: https://doi.org/10.24321/2454.8650.202301